Mellem kommunikation og kreativitet – deltagelse som æstetikkens missing link? - Eriksson, Birgit (K&K - Kultur og Klasse, 2014)
The French philosopher Yves Michaud modernity has characterised modernity by three utopias: the utopia of democratic citizenship, which deals with freedom and equality; the utopia of labour, which deals with social change; and the utopia of art, which deals with inter-subjective communication and community. He has argued that the utopia of art, which since the late 18th century has been closely linked to the utopia of democratic citizenship, is coming to an end. Building upon this argument, the article examines two opposing tendencies in contemporary art and culture: On the one hand, the creativity and promise of novelty, traditionally belonging to the art world, has spread culturally, and creativity is often represented as the most important tool for individual and social change. On the other hand, the idea of art as sustaining participation has been revitalized in the art world by the “relational” or “social” aesthetics, and the “dialogical” or “participatory” art of the last 20 years. But how do these tendencies relate to the modern utopia of art – and to each other? What are the problems inherent in relating art to beautiful ideals of community and creativity, and (how) can the recent focus on aesthetic participation transgress these problems? The article examines these questions, drawing on theories and an analysis of contemporary culture.